Melatonin Synthesis: Acetylserotonin O-Methyltransferase (ASMT) Is Strongly Expressed in a Subpopulation of Pinealocytes in the Male Rat Pineal Gland - Rath, Martin F. (Endocrinology, 2016)
The rat pineal gland has been extensively used in studies of melatonin synthesis. However, the cellular localization of melatonin synthesis in this species has not been investigated. Here we focus on the localization of melatonin synthesis using immunohistochemical methods to detect the last enzyme in melatonin synthesis, acetylserotonin O-methyltransferase (ASMT), and in situ hybridization techniques to study transcripts encoding ASMT and two other enzymes in melatonin synthesis, tryptophan hydroxylase (TPH)-1 and aralkylamine N-acetyltransferase. In sections of the rat pineal gland, marked cell-to-cell differences were found in ASMT immunostaining intensity and in the abundance of Tph1, Aanat, and Asmt transcripts. ASMT immunoreactivity was localized to the cytoplasm in pinealocytes in the parenchyma of the superficial pineal gland, and immunopositive pinealocytes were also detected in the pineal stalk and in the deep pineal gland. ASMT was found to inconsistently colocalize with S-antigen, a widely used pinealocyte marker; this colocalization was seen in cells throughout the pineal complex and also in displaced pinealocyte-like cells of the medial habenular nucleus. Inconsistent colocalization between ASMT and TPH protein was also detected in the pineal gland. ASMT protein was not detected in extraepithalamic parts of the central nervous system or in peripheral tissues. The findings in this report are of special interest because they provide reason to suspect that melatonin synthesis varies significantly among individual pinealocytes.